Use of Online Information Resources for Knowledge Organisation in Library and Information Centres: A Case Study of CUSAT - S.N., Archana; Padmakumar, P.K. (DESIDOC Journal of Library & Information Technology, 2010)
The paper discusses the use of online information resources for organising knowledge in library and information centres in Cochin University of Science and Technology (CUSAT). The paper discusses the status and extent of automation in CUSAT library. The use of different online resources and the purposes for which these resources are being used, is explained in detail. Structured interview method was applied for collecting data. It was observed that 67 per cent users consult online resources for assisting knowledge organisation. Library of Congress catalogue is the widely used (100 per cent) online resource followed by OPAC of CUSAT and catalogue of British Library. The main purposes for using these resources are class number building and subject indexing. http://dx.doi.org/10.14429/djlit.31.1.758